THE ISRAELI-PALESTINIAN-JORDANIAN CONFEDERATION ALTERNATIVE. (December 2022) - Schenker, Hillel
There is an international consensus that the two-state solution, the establishment of a Palestinian state in the West Bank and Gaza with East Jerusalem as its capital, should be the basis for the resolution of the Israeli-Palestinian conflict. Given the current right-wing tendencies within Israeli politics, I ask if the way to break the current impasse in Israeli-Palestinian relations might be to try to return the Jordanian factor to the equation as Alon Ben-Meir has recently proposed .